PENGARUH PENGGULUDAN DAN PUPUK KANDANG TERHADAP PERTUMBUHAN DAN PRODUKSI HIJAUAN RUMPUT PAKAN PADA TANAH SALIN - F Kusmiyati; Rahayuning Tri Mulatsih; Adriani Darrnawati (JURNAL LITBANG PROVINSI JAWA TENGAH, 2002)
Plants growing in saline conditions usually face toxicity problems, especially Sodium (Ma) toxicity that often leads to crop failene. The research was conducted to evaluate the effect of bed type and manure on growth and herbage yield of forage crop in salin soil. The experiment was arranged in split plot design with three replication. The first factor as main plot was bed type: G 1 (without bed type) and 02 (with bed type). The second factor as sub plot was dosage of manure which was devided into 4 levels KI (0 kg N/ha), K2 (50 Kg Nzha), K3 ( I 00 kg N/ha) and K4 ( 150 kg N/ha). The parameters were observed in this experiment: plant, height, leaf number, fresh yield, dry yield, level of death and Sodium content in soil (ppm). Data were analizcd by analysis of variance. The differences among means were determined by using Duncan's Multiple Range Test. The result showed that the application of manure increased leaf number, fresh yield and dry yield significantly (p<0.05). Application of manure decreased the level of death and Na content in soil significantly (p<0.05). There was no effect of using bed type on leaf number, fresh yield. dry yield, level of death and Na content in soil.